Parâmetros genéticos de características de carcaça e de crescimento de bovinos da raça Nelore - Ferriani, L.; Albuquerque, L. G. [UNESP]; Baldi, F. S B [UNESP]; Venturini, G. C. [UNESP]; Bignardi, A. B. [UNESP]; Silva, J. A. [UNESP]; Chud, T. C. S. [UNESP]; Munari, D. P. [UNESP]; Oliveira, J. A. [UNESP] (SciELO Espana/Repisalud, 2013)
The objectives of this study were to estimate genetic parameters involving yearling weight (Ps), carcass weight (Pc), hip height (Ag) and the scores of conformation (C), precocity (P) and musculature (M) and carcass yield (Rd) and finishing score (Ac) in Nellore cattle in order to define criteria for selection in this breed. The data of the 20 732 animals were obtained from Agrope-cuária Jacarezinho, SP. Data were analyzed by restricted maximum likelihood using animal model multi-trait analysis, which included fixed effects of contemporary groups (animals born at the same month and slaughtered on the same day) and the covariate age at slaughter (linear) for carcass traits, and contemporary groups (animals of the same farm, age, sex and management group at weaning and yearling) and yearling age (linear) for growth and as random, the additive effects and residual effects. Estimates ranged from 0.13 (Ac and Rd) to 0.36 (Ag) for heritability and from -0.59 ± 0.62 (Rd with Ac) to 0.71 ± 0.17 (Pc with C) for genetic correlations. Selection for Pc, C, P, M, Ag or Ps may be efficient because their heritability estimates are of magnitude moderate. Selection for Ps and C can favor heavier Pc, considering their positive and high genetic correlation.
Genetic parameters of carcass and growth traits of Nellore cattle
Keywords: Conformation; Musculature; Precocity; Yearling weight